SYNERGISTIC BIODEGRADATION OF SYNTHETIC TEXTILE DYES USING A HYBRID ALGOPHYTOSYSTEM CONSORTIUM OF CHLORELLA VULGARIS, AZOLLA FILICULOIDES, AND LEMNA MINOR (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
Textile industrial effluents containing recalcitrant synthetic dyes pose a severe threat to aquatic ecosystems due to their high toxicity and resistance to conventional treatment. This study investigates the synergistic biodegradation efficiency of a hybrid algophytosystem consortium comprising the microalga Chlorella vulgaris and the macrophytes Azolla filiculoides and Lemna minor. Experiments were conducted over a 14-day cultivation period using simulated textile wastewater containing Methylene Blue (MB, 50 mg/L) and Reactive Red 120 (RR120, 50 mg/L). The integrated consortium demonstrated superior decolorization performance, achieving 92.5% removal for MB and 88.7% for RR120, compared to monocultures which stagnated below 72%. Furthermore, the Chemical Oxygen Demand (COD) was reduced by 81.4%. Enzymatic assays revealed a significant upregulation of laccase and peroxidase activity, confirming that biodegradation rather than mere biosorption was the primary mechanism. This novel integrated biotechnology provides an eco-friendly, cost-effective blueprint for advanced textile wastewater remediation.
Keywords: Algophytosystem, Chlorella vulgaris, Azolla filiculoides, Lemna minor, Synthetic dyes, Biodegradation, Textile effluent, Synergy.